Assessment of the Status of National Oral Health Policy in India - Nandita Rani Kothia; Vikram Simha Bommireddy; Talluri Devaki; Narayana Rao Vinnakota; Srinivas Ravoori; Suresh Sanikommu; Srinivas Pachava (Kerman University of Medical Sciences, 2015)
Background National oral health policy was conscripted by the Indian Dental Association (IDA) in 1986 and was accepted as an integral part of National Health Policy (NHP) by the Central Council of Health and Family Welfare in one of its conferences in the year 1995. Objectives of this paper were to find out the efforts made or going on towards its execution, its current status and recent oral health-related affairs or programs, if any. Methods Literature search was done using the institutional library, web-based search engines like 'Google' and 'PubMed' and also by cross referencing. It yielded 108 articles, of which 50 were excluded as they were not pertinent to the topic. Twenty-four were of global perspective rather than Indian and hence were not taken into account and finally 34 articles were considered for analyses. Documents related to central and state governments of India were also considered. Results All the articles considered for analysis were published within the past 10 years with gradual increase in number which depicts the researchers' increasing focus towards oral health policy. Criticisms, suggestions and recommendations regarding national oral health programs, dental manpower issues, geriatric dentistry, public health dentistry, dental insurance, oral health inequality, and public-private partnerships have taken major occupancies in the articles. Proposals like "model for infant and child oral health promotion" and "oral health policy phase 1 for Karnataka" were among the initiatives towards national oral health policy. Conclusion The need for implementation of the drafted oral health policy with modification that suits the rapidly changing oral health system of this country is inevitable.